Pelatihan Pengembangan Kreativitas Guru Dalam Pembuatan Media Pembelajaran Interaktif - Agusti Agusti Mardikaningsih; Praharisti Kurniasari (Pusat Riset Manajemen dan Publikasi Ilmiah Serta Pengembangan Sumber Daya Manusia Sinergi Cendikia, 2022)
In the current technological era, the learning process that occurs in educational institutions has undergone very significant changes, one of which is the use of learning media as access to information delivery. Learning is a process of communication interaction between learners and teachers. Communication will not run without the help of the means of conveying messages or media. Based on the analysis of the existing situation, the service team held training activities for making interactive learning media for junior high school teachers by utilizing the program power point. This training was attended by 24 teachers from various schools. The meetings were held for 10 times using direct practical training methods and assignments. The implementation of this service activity was deemed successful in developing the creativity of teachers seen from the teachers who had attended the training activities and had completed creating an interactive learning media in accordance with the subjects taught at school.